Combination of nitrogen and organic fertilizers reduce N2O emissions while increasing winter wheat grain yields and quality in China - Jin, Yakang; Chen, Hong; Tang, Xiaoqian; Zhang, Lei; Yan, Jun; Li, Shuangjun; Chen, Ya; Li, Xinwei; Wu, Hongbao; Xiao, Xin (Frontiers in Environmental Science, 2024)
Wheat grain yields, quality, and nitrous oxide (N2O) emissions were controlled through the type and application rate of nitrogen (N) fertilizer. Here, we investigated the optimal management of N fertilization by examining the combined effects of organic and N fertilizers on wheat yields, quality, and N2O emissions. Field trials under six treatments were located on campus farms at Anhui Science and Technology University, including farmer's common practice (270 kg N ha -1 , N270), 2/3 reduction in N270 (90 kg N ha -1 , N90), organic fertilizer with equal N270 (OF270), 2/3 reduction in OF270 (OF90), 4/5 reduction OF270 + 1/5 reduction N270 (20% OF270 + 80% N270), and 4/5 reduction OF90 + 1/5 reduction N90 (20% OF90 + 80% N90) were applied to winter wheat.The plots were arranged in a randomized complete block experimental design. The N2O emissions were quantified under different fertilization measures in the peak wheat growing season during sowing, jointing, and grain filling stages, respectively. Compared with N270 and N90 treatments, N2O emissions were significantly decreased by 18.6% and 27.2%, respectively, under 20% OF270 + 80% N270 and 20% OF90 + 80% N90 (P < 0.05). Further, The prudent application of N fertilizers can increase wheat yields, improve their quality, and decrease N2O emissions from wheat field soils.